1991
DOI: 10.1073/pnas.88.9.3912
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of epidermal growth factor on adipose tissue development in vivo.

Abstract: The ability of epidermal growth factor (EGF) to affect adipose tissue development in vivo was investigated. The subcutaneous administration of EGF to newborn NBR rats for 10 days resulted in decreased body weight and fat pad weight that occurred in a dose-dependent fashion. At a dose of 1 ,Ig/g of body weight, injected EGF resulted in a 50% decrease of fat pad weight. Although kidney weight was also diminished, the weight of other organs such as liver and intestine remained unchanged or even slightly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
3
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 30 publications
6
32
3
1
Order By: Relevance
“…Available data in rats are consistent with a role of EGF on adipose tissue development. In newborn rats, daily EGF injections decrease both body and fat pad weight gains with no effects on other organs (Serrero and Mills, 1991). The number of adipocyte precursors per fat pad is higher in fat pads from EGF-treated animals than in control rats, but triglyceride storage in these tissues is lower.…”
Section: Leptinmentioning
confidence: 90%
“…Available data in rats are consistent with a role of EGF on adipose tissue development. In newborn rats, daily EGF injections decrease both body and fat pad weight gains with no effects on other organs (Serrero and Mills, 1991). The number of adipocyte precursors per fat pad is higher in fat pads from EGF-treated animals than in control rats, but triglyceride storage in these tissues is lower.…”
Section: Leptinmentioning
confidence: 90%
“…Moreover, primary rat adipogenic precursor cells are also inhibited from becoming adipocytes in the presence of EGF (14), and EGF-treated animals show retardation of the development of adipose tissue (16). Although the precise mechanism of this …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EGF has a dual effect on fat synthesis [42,43]. It decreases adipogenesis in undifferentiated preadipocytes but increases adipogenesis in differentiated adipocytes [44].…”
Section: Discussionmentioning
confidence: 99%